Transition economy convergence in a two-country model: implications for monetary integration - Jan Bruha; Jirí Podpiera (European Central Bank (ECB), 2007)
In this paper we present a two-country dynamic general equilibrium model of ex ante unequally developed countries. The model explains a key feature recently observed in transition economies – the long-run trend real exchange rate appreciation – through investments into quality. Our exchange-rate projections bear important policy implications, which we illustrate on the collision between the price and nominal exchange rate criterion for the European Monetary Union in a set of selected transition economies in Central and Eastern Europe.
Keywords: E58; F15; F43; 330; convergence; Currency area; monetary policy; Two-country modeling; Zwei-Länder-Modell; Allgemeines Gleichgewicht; Wirtschaftliche Konvergenz; Währungsunion; Theorie; Entwicklungsländer